MODEL SANKSI BAGI FASILITAS LAYANAN KESEHATAN YANG MENGGUNAKAN OBAT KEDALUARSA - Vitrianingsih, Yeni (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Pharmaceutical services are services that are directly provided to patients and are responsible for treating patients, so it is hoped that hospitals can provide optimal pharmaceutical services to achieve definite results and improve the quality of life of patients. Medication management is one aspect of hospital management that is very important in providing overall health services, so that it can guarantee patient treatment. This research uses a normative juridical method. Health service facilities must strive to carry out service activities in accordance with applicable laws and regulations, because if there are forms of administrative violations that can be legally proven, then the service facility that commits the violation may be subject to administrative sanctions. Forms of administrative violations of health service facilities. Forms of administrative violations if committed by health service facilities in working relationships with health workers, as stipulated in Law Number 36 of 2014 concerning Health Workers, can be subject to administrative sanctions. Imposing administrative sanctions on health service facilities. The imposition of administrative sanctions is part of the law enforcement process to control, supervise and take action against health service facilities that commit administrative violations. The application of administrative sanctions must of course be carried out in accordance with the form of the violation that occurred. Law Number 36 of 2014 concerning Health Workers, Article 82 paragraph (2) Every health service facility that does not implement the provisions of Article 26 paragraph (2), Article 53 paragraph (1), Article 70 paragraph (4), and Article 74 is subject to administrative sanctions